N-Centered Chiral Self-Sorting and Supramolecular Helix of Tröger's Base-Based Dimeric Macrocycles in Crystalline State - Chen, Yuan; Cheng, Ming; Hong, Benkun; Zhao, Qian; Qian, Cheng; Jiang, Juli; Li, Shuhua; Lin, Chen; Wang, Leyong (Frontiers in Chemistry, 2019)
Three stereoisomers of Tröger’s Base-based dimeric macrocycles Trögerophane 1 (T1) including one pair of enantiomers (rac-T1) and one meso isomer (R2NS2N-T1) were obtained and fully characterized by X-ray analysis. In the crystalline stacking state R2NS2N-T1 showed heterochiral self-sorting behavior along a axis with cofacial π-π stacking interactions, while rac-T1 showed heterochiral self-sorting behavior along c axis with slipped π-π stacking interactions, respectively. Meanwhile both of them showed homochiral self-sorting behavior along b axis as well as one pair of supramolecular helixes were formed in both cases. All the self-sorting behaviors are controlled by two chiral Tröger’s Base units from neighbouring molecules. To the best of our knowledge, such chiral self-sorting and supramolecular helixes of N-centered chiral superstructures is a rare example. In addition, R2NS2N-T1 and rac-T1 demonstrated different adsorption capacities towards the vapor of dichloromethane and acetone, respectively.